2018
DOI: 10.1080/14763141.2018.1461915
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic differences in upper limb joints between flat and topspin forehand drives in competitive male tennis players

Abstract: The topspin tennis forehand drive has become a feature of modern game; yet, as compared to the serve, there has been little research analysing its kinematics. This is surprising given that there is considerably more variation in the execution of the topspin forehand. Our study is the first to examine the amplitude of upper limb joint rotations that produce topspin in the forehand drives of 14 male competitive tennis players using video-based motion analysis. Humerothoracic abduction (-)/adduction (+), extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
4
26
0
Order By: Relevance
“…Our finding that flat forehands have a significantly higher ball speed than topspin forehands is in agreement with a study by Genevois et al. 10 Although faster racket head velocity results in a greater speed of the ball leaving the racket, 12 as mentioned previously, the study by Rota et al. 14 found no significant difference in ECR and FCR activity levels for flat forehands hit at different speeds.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our finding that flat forehands have a significantly higher ball speed than topspin forehands is in agreement with a study by Genevois et al. 10 Although faster racket head velocity results in a greater speed of the ball leaving the racket, 12 as mentioned previously, the study by Rota et al. 14 found no significant difference in ECR and FCR activity levels for flat forehands hit at different speeds.…”
Section: Discussionsupporting
confidence: 93%
“…36 found stress fractures of the second metacarpal in the hand were associated with increased tennis playing intensity and may be associated with use of the semi-western or western forehand grip. Although previous studies typically grouped the different forehand grip positions together, 10,14 the separate analysis of the different forehand grip positions on the potential development of elbow tendinopathy could provide vital information for coaches when recommending the different forehand grip positions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, (Johnson & McHugh, 2006) reported that the short duration of backswing would result in a higher anterior shoulder force in the backswing phase. Therefore, to prevent shoulder and elbow injuries due to overload movements, the player should pay attention to the maximum shoulder back swing in a chain (Genevois et al, 2020).…”
Section: Discussionmentioning
confidence: 99%